Impact of leaf trichomes of tomatoes and weeds on the host selection and developmental bioassays of Bemisia tabaci Q and A cryptic species - Md Mostafizur Rahman Shah; Zhongkai Zhang; Jian Hu; Ahmed Gaber; Akbar Hossain (Heliyon, 2023)
The whiteflies of Bemisia tabaci complex, composed of >44 cryptic species, are economically important pests of tomatoes for their direct feeding and virus transmission. The present study aimed to evaluate the impact of leaf trichomes on the host selection and development of whitefly; comparative invasiveness between B. tabaci Q and A cryptic species; and the ability of weeds as hosts of the population of insect whitefly. We carried out our investigation through adult host selection and oviposition in multi-choice conditions, immature development and survival, and adult survival and oviposition in no-choice conditions. We investigated leaf trichomes type and densities on the leaves of four tomato varieties and two weed species. Results showed that the leaf trichomes of tomatoes and weeds impact the host selection and immature development differently on the cryptic species B. tabaci Q and A. In the multi-choice case, B. tabaci Q adults preferred tomato varieties Ao-Ni-Er and He-Fen for both settling and oviposition whereas B. tabaci A preferred Ao-Ni-Er, He-Fen, and Billy-Goat-Weed for settling but oviposited more eggs on both weed species Billy-Goat-Weed and False-Mallow. Both B. tabaci Q and A adults refused Ye-Sheng either settling or oviposition. In the case of immature development, B. tabaci Q developed faster than B. tabaci A. Concerning plant, B. tabaci Q developed faster on Ao-Ni-Er, He-Fen and Billy-Goat-Weed but B. tabaci A on Billy-Goat-Weed, False-Mallow and Ao-Ni-Er. The immature survival of Q was higher than that of A. Immature of B. tabaci Q survived well (68.6–86.8%) on all plants except Ye-Sheng (49.3%) but B. tabaci A survived very less (0–17.6%) on any tomatoes where 70.4% on Billy-Goat-Weed and 60.5% on False-Mallow. After seven days of adult infestation, both B. tabaci Q and A died on Ye-Sheng where 52.5–78.1% survivorships were observed on other plants. In seven days, B. tabaci Q laid more eggs compared to B. tabaci A. Considering the plants, both species laid more eggs on Ao-Ni-Er, He-Fen and False-Mallow, whereas the lowest number was laid on Ye-Sheng. The highest number of glandular trichome Type IV was observed on Ye-Sheng which showed resistance against both B. tabaci Q and A cryptic species. The cryptic species B. tabaci Q showed a wider range adaptation ability on plants than that of A. Weeds can play a significant role as an infestation source of whiteflies to tomatoes and other crops. These findings suggest that glandular trichomes may be used in plant breeding programmes for the development of whitefly-resistant crop cultivars.